Master planning affordable housing: streamlining the creation of affordable housing for Manhattan Kansas, and other cities - Paulson, Alyssa Ann Jolene (Kansas State University, 2024)
In 2022, city planners in Manhattan, Kansas, identified a need for expanding mid-to-low-income housing stock within the city through a comprehensive housing market analysis. To meet the projected demand for over 2,000 additional dwelling units in the next two decades, implementing strategies to increase affordable housing stock will be imperative. Given the historical involvement of landscape architects in master planning and neighborhood amenity development, a thorough exploration of affordability factors: site selection, site infrastructure, housing selection, and overall site design by landscape architects could contribute to innovative affordable communities. This study is grounded through a literature review, an examination of precedent projects that highlight aspects of affordable housing, and a review of Manhattan’s financial conditions. Collecting data from the literature review, precedents, and financial data in Manhattan was used to inform an application of the affordability factors on a local site. Projective designs were used to illustrate and summarize strategies to reduce the cost of owned housing that can be applied to other cities.
Keywords: Affordable housing; Master planning; Site layout; Landscape architecture; Site infrastructure; Affordable community design